Mutagenicity of Tectona grandis Wood Extracts and Their Ability to Improve Carbohydrate Yield for Kraft Cooking Eucalyptus Wood - Yulia Anita; Syelvia Putri Utami; Hiroshi Ohi; Evelyn Evelyn; Akiko Nakagawa-Izumi (Molecules, 2021)
Considering the toxicity of the impurities of synthesized anthraquinone, this study clarified new catalytic compounds for kraft cooking with improved carbohydrate yield and delignification and less mutagenicity, which are important for ensuring the safety of paper products in contact with food. The 2-methylanthraquinone contents of teak (Tectona grandis) woods were 0.18–0.21%. Acetone extracts containing 2-methylanthraquinone from Myanmar and Indonesia teak woods as additives improved lignin removal during kraft cooking of eucalyptus wood, which resulted in kappa numbers that were 2.2–6.0 points lower than the absence of additive. Myanmar extracts and 2-methylanthraquinone improved carbohydrate yield in pulps with 1.7–2.2% yield gains. Indonesia extracts contained more deoxylapachol and its isomer than 2-methylanthraquinone. The residual content of 2-methylanthraquinone in the kraft pulp was trace. Although Ames tests showed that the Indonesia and Myanmar extracts were mutagenic to Salmonella typhimurium, 2-methylanthraquinone was not. The kraft pulp obtained with the additives should be safe for food-packaging applications, and the addition of 0.03% 2-methylanthraquinone to kraft cooking saves forest resources and fossil energy in industries requiring increased pulp yield.